Design Of Safety Hoist Lifting System On Electric Container Crane Based Programmable Logic Controller Omron Type CP1E-E20DR-A And Microsoft Visual Basic - Eddo Mahardika; Feri Firmanto; Dwi Songgo Panggayudi (Jurusan Teknik Elektro Universitas Trunojoyo Madura, 2019)
Electric container cranes that exist today still have shortcomings in the safety hoist lifting system. Safety is less reliable resulting in the accident when the lifting hoist process runs, the case that often happens is the fall of containers during the appointment process. The other problem, safety hoist lifting system can not be monitored by computer in the spreader system. This study improves the existing safety hoist lifting system deficiencies by designing and constructing the electric container crane model which safe and efficient using the Programmable Logic Controller Omron CP1E-E20DR-A as a safety system and Visual Basic as Human Machine Interface (HMI). PLC was chosen in this study because it is flexible in programming. HMI program using Visual Basic and Arduino Uno R3 was chosen because it is cheaper.The use of PLC in safety hoist lifting system is very effective because the reversible counter and timer programs can replace the functions of cam switches and overspeed switches that are less effective. The addition of HMI proved to be easier in the monitoring system. Safety hoist lifting system in electric container crane safe and efficient can be built with PLC and Visual Basic with a lower cost has been able to provide convenience in the monitoring system.Keywords: container crane, safety, hoist lifting, interlock